Growth patterns during and after treatment in patients with pediatric ALL: A meta‐analysis. Issue 8 (24th March 2015) - Zhang, Fang Fang; Liu, Shanshan; Chung, Mei; Kelly, Michael J.
Abstract : Background: Survivors of pediatric acute lymphoblastic leukemia (ALL) have a significantly higher body mass index (BMI) than their peers. Understanding the critical time periods in which patients with pediatric ALL are vulnerable to unhealthy weight gain will lay the groundwork for developing effectively timed interventions. Procedure: We determined the growth patterns of patients with pediatric ALL during and after treatment through the conduct of a systematic review and meta‐analysis. A search of MEDLINE, Scopus, and Web of Science was performed from its inception through May 2014. Studies met the inclusion criteria if they included at least 10 patients of pediatric ALL, and longitudinally assessed BMI at diagnosis and at least one time point after diagnosis Results: Twenty‐one studies met the inclusion criteria for the systematic review and 16 were included in meta‐analysis. The mean increase in BMI z‐score during treatment in 1, 514 patients with pediatric ALL was 0.81 (95% CI: 0.25–1.38). Specifically, patients experienced substantial weight gain in early treatment (Δ = 0.41, 95% CI: −0.34, 1.17) and again during maintenance (Δ = 0.34, 95% CI:−0.22, 0.90). The mean increase in BMI z‐score ranged between 0.52 and 0.89 beyond treatment completion. Subgroup analyses found unhealthy weight gain occurred regardless of patients' receipt of cranial radiation therapy, sex, and, weight status at diagnosis. Conclusions: Patients with pediatric ALL experience unhealthy weight gain early in treatment, and increases in weight are maintained beyond treatment completion. Preventing early onset of obesity is a priority for improving the care and outcomes for patients with pediatric ALL. Pediatr Blood Cancer 2015;62:1452–1460. © 2015 Wiley Periodicals, Inc.